Entrepreneurship Education in the Transnational Vocational Education Context - Pimpa, Nattavud (Journal of Technical Education and Training, 2019)
Entrepreneurship education is often perceived from the local context, due to the lack of international exposure of the local stakeholders in this area. Learning and teaching entrepreneurship education as part of the technical and vocational education and training (TVET) in the transnational context, therefore, is relatively new. In fact, it remains unclear on what kind of learning is appropriate for the future entrepreneurs who need to work in the global business context. In this paper, we explore learning experiences of undergraduate students in the transnational entrepreneurship education program, focusing on vocational and career training, co-offered by two partners from Australia and Singapore. We focus on what Singaporean students identified as challenges in learning in the transnational entrepreneurship education program in the Australian context from the Singaporean view. This study unfolds the complexity of the management of transnational entrepreneurship education, engagements among students from different locations, and cross-cultural bias in the management of program, people, and learning. It is suggested that addressing these challenges require managers of transnational entrepreneurship education programs to consider issues of power and inequality inherent in teaching partnerships, industry engagement, and the mindset change needed to develop global perspectives.